The Influence of Financial Literacy, and Investment Knowledge on Investment Interest mediated by Investment Motivation - Juliati Pratiwi, Ni Putu Vera; Ardana Putra, I Nyoman Nugraha; Auliana Soesetio, Raden Roro Dhiya; Suryani, Embun (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 1 (2024): Vol. 17, No. 1, Februari 2024 (pp.1-154)DO - 10.24843/JEKT.2024.v17.i01.p05, 2024)
This study attempted to determine the influence of investment knowledge and financial literacy on capital market investing interest via investment motivation. All IDX Investment Gallery users in the Faculty of Economics and Business, University of Mataram, made up the study's population, and 85 Investment Gallery users were chosen as the study's sample using a purposive selection approach. Associative quantitative research is the term used to describe this sort of study. Smart-PLS 4 was utilized to process the data in this study, and the following tests were run: validity test, reliability test, R-Square, inner model, and path coefficient. The findings demonstrated that, while investment knowledge has a negligible impact on investment interest, financial literacy, and investment motivation have a favorable and considerable impact. Investment motivation is positively and significantly impacted by financial knowledge and literacy. Financial literacy and investment interest can be mediated by investment motive, but investment knowledge cannot.